A Path Analysis on the Factors Associated with Birth Preparedness: Evidence from Wonogiri, Central Java - Ummah, Hafari Fajria Nuril; Pamungkasari, Eti Poncorini; Adriani, Rita Benya (Journal of Maternal and Child Health, 2019)
Background: Birth preparedness and complication readiness is a strategy that encourages pregnant women, their families, and communities to effectively plan for births and deal with emergencies, if they occur. It is a key component of globally accepted safe motherhood programs. This study aimed to determine factors associated with birth preparedness in Wonogiri, Central Java. Subjects and Method: This was a cross-sectional study carried out in Wonogiri, Central Java, from April to May 2018. A sample of 200 pregnant women was selected by cluster sampling. The dependent variable was birth preparedness. The independent variables were gestational age, parity, maternal education, maternal knowledge on birth sign, husband support, and health personnel role. The data were collected by questionnaire and analyzed by path analysis, run on Stata 13. Results: Birth preparedness was positively affected by good maternal knowledge on birth sign (b=2.97; 95% CI=0.10 to 5.84; p=0.043), husband support (b=5.06; 95% CI=2.62 to 7.51; p<0.001), and health personnel role (b=5.53; 95% CI=2.95 to 8.11; p<0.001). Birth preparedness was indirectly affected by gestational age, maternal education, and parity. Conclusion: Birth preparedness is positively affected by good maternal knowledge on birth sign, husband support, and health personnel role. Birth preparedness is indirectly affected by gestational age, maternal education, and parity. Keywords: birth preparedness, gestational age, education, knowledge, husband support, health personnel role Correspondence: